Sistem Informasi Penambahan PTK di GTK Dinas Pendidikan Kota Tanjung Balai - Sofyan Marpaung (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information and communication technology has significantly transformed various sectors, including education. The Education Office of Tanjungbalai City faces challenges in efficiently managing teaching and educational staff (PTK). This report discusses the development of the Information System for PTK Addition in GTK at the Tanjungbalai City Education Office, aimed at facilitating the registration and management of new educational personnel. The Multifactor Evaluation Process (MFEP) method was used in analyzing and making decisions for this system. The proposed system is web-based, enabling structured recording and monitoring of PTK. The implementation of this system is expected to enhance efficiency in educational staff administration and ensure transparency in the recruitment and placement process.